PERBEDAAN PENGARUH LATIHAN ONE HAND SET SHOOT DAN TWO HAND SET SHOOT TERHADAP TEMBAKAN BEBAS (FREE THROW) DALAM PERMAINAN BOLA BASKET PADA ATLET BALKA CLUB TAHUN 2020 - Maulana Iqbal; Agustanico Dwi Muryadi; Karlina Dwijayanti (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2021)
The aims of this study were: (1) To determine the effect of one hand set shoot practice on free throws in basketball games. (2) Knowledge of the effect of the two hand set shoot exercise on free throws in basketball games. (3) Knowing the difference in the effect between one hand set shoot and two hand set shoot exercises on free throws in basketball games. The research method used is the experimental method. The subjects in this study were Balka Club athletes number 30 participants in Purwodadi Village, Purwodadi District, Grobogan Regency in 2020. The collection technique to obtain the data needed in this study used a one-handed and two-handed shot test against free throws. results based on data analysis: There is a significant effect of one-handed shooting practice on basketball free throws in Balka Club 2020 athletes (1). There is a significant effect of two-handed shooting practice on basketball free throws for Balka Club 2020 athletes (2). There is a significant difference in the effect of one-handed and two-handed shooting practice on basketball free shots for Balka Club 2020 athletes. From the calculations that have been made, the t-value is 0.879, it is smaller (table 5%) which is 2.131. Two-handed shooting training has a better effect on basketball free throw skills for Balka Club 2020 athletes. The increase in free throw practice skills in group 2 (the group receiving two-handed training) is 92% > group 1 (the group that received the one-handed shot practice treatment) was 74% (3).